Epidermal growth factor and oncogenes induce transcription of the same cellular mRNA in rat fibroblasts. - Matrisian, L M (1985)
We have isolated and sequenced a cloned cDNA corresponding to an mRNA present in significantly higher levels in rat cells transformed by polyoma virus, Rous sarcoma virus, and the cellular oncogene H-ras than in the normal parental cell lines. The mRNA transcript is also rapidly induced by the polypeptide growth factor epidermal growth factor, providing a new link between oncogenes and growth factors. Both the growth factor and the oncogenes control expression of the corresponding gene at the transcriptional level. Our results point to the existence of intracellular mechanisms that are common to the action of both growth factors and oncogenes.